Co-based Fuel Cell Cathode Electrocatalyst for both Acid and Alkaline Environment. (February 2019) - Jiang, Tao; Luan, Weiling; Wu, Senming
Abstract: The development of a cheap and high-performance oxygen reduction reaction (ORR) catalyst is still a great issue for fuel cells. Co-N-C is found good ORR catalytic activity as the substitute of the present precious-metal platinum and its alloys. Herein, we propose an ORR catalyst doped with Co and N, which shows excellent catalytic activity in alkaline media with half-wave potential of 10 mV positive than commercial Pt/C 20 wt.%, and comparable catalytic activity in acid electrolyte with half-wave potential of 118 mV negative than Pt/C. Besides, as-prepared catalyst shows high durability in both alkaline and acid environment, attributing to the synergistic effect of the Co-Nx active sites and the coexistence of amount pyridinic nitrogen and graphitic nitrogen.